A new ecological risk assessment index for metal elements in sediments based on receptor model, speciation, and toxicity coefficient by taking the Nansihu Lake as an example. (June 2018) - Zhuang, Wen; Wang, Qian; Tang, Lebin; Liu, Jinhu; Yue, Wen; Liu, Yongxia; Zhou, Fengxia; Chen, Qing; Wang, Mantang
Highlights: A new ecological risk assessment index for metals in sediment was established. The toxicity coefficients of Be, Sb and Tl were calculated and determined. Be and Sb were mainly from human activity and introduced mineral sources. Tl was mainly from inherent mineral sources. Abstract: This study focuses on the establishment of a new ecological risk assessment method called as multiparameter evaluation index (MPE) by a combination of speciation, toxicity coefficient, and receptor model of metal elements in sediments and the application of MPE in the assessment of ecological risks of Be, Sb, and Tl in the Nansihu Lake. Because of lack of toxicity coefficient values for Be, Sb, and Tl, their toxicity coefficients were calculated in this study. Speciation analysis showed that Sb had better mobility and bioavailability than Be and Tl. Source apportionment results showed that Be and Sb were mainly from human activities and introduced minerals. Tl was mainly an inherent mineral. MPE results showed that the degree of ecological risk was Be > Sb ≫ Tl. MPE could distinguish the ecological risk levels more accurately than current indices such as RI and RAC.